All-solution-based aggregation control in solid-state photon upconverting organic model composites - Goudarzi, Hossein; Keivanidis, Panagiotis E. (My University, 2017)
Hitherto, great strides have been made in the development of organic systems that exhibit triplet-triplet annihilation-induced photonenergy upconversion (TTA-UC). Yet, the exact role of intermolecular states in solid-state TTA-UC composites remains elusive. Here we perform a comprehensive spectroscopic study in a series of solution-processable solidstate TTA-UC organic composites with increasing segregated phase content for elucidating the impact of aggregate formation in their TTA-UC properties. Six different states of aggregation are reached in composites of the 9,10-diphenylanthracene (DPA) blue emitter mixed with the (2,3,7,8,12,13,17,18-octaethylporphyrinato)platinum(II) sensitizer (PtOEP) in a fixed nominal ratio (2 wt % PtOEP). Fine-tuning of the PtOEP and DPA phase segregation in these composites is achieved with a lowtemperature solution-processing protocol when three different solvents of increasing boiling point are alternatively used and when the binary DPA:PtOEP system is dispersed in the optically inert polystyrene (PS) matrix (PS:DPA:PtOEP). Time-gated (in the nanosecond and microsecond time scales) photoluminescence measurements identify the upper level of PtOEP segregation at which the PtOEP aggregate-based networks favor PtOEP triplet exciton migration toward the PtOEP:DPA interfaces and triplet energy transfer to the DPA triplet manifold. The maximum DPA TTA-UC luminescence intensity is ensured when the bimolecular annihilation constant of PtOEP remains close to γTTA-PtOEP = 1.1 × 10-13 cm3 s-1. Beyond this PtOEP segregation level, the DPA TTA-UC luminescence intensity decreases because of losses caused by the generation of PtOEP delayed fluorescence and DPA phosphorescence in the nanosecond and microsecond time scales, respectively.
Keywords: Energy migration; Exciton hopping; Phosphorescence; Photon upconversion; Sensitization; Triplet fusion